Brazil-china bilateral link during the 21st century: business as usual - Ceppi, Natalia Paola (2024)
Throughout 50 years of bilateral relations, the link between Brazil and China was built slowly but steadily, reaching an unusual dynamism in the 21st century. This was the result of State policies, which found in their counterpart fertile ground for their own foreign policy to flourish, as well as an important economic and commercial complementarity. For this reason, the aim of this article is to examine China´s rise on Brazil´s foreign agenda over the course of this century, paying special attention to existing commercial interests, particularly in the energy sector. Chinese penetration since 2000 has maintained continuity and dynamism, regardless the ideological turnovers, since trade and energy business have become its backbone. While the PT governments took the political and economic dimensions of diplomacy towards China along the same track, Bolsonaro´s administration decoupled these dimensions, although he had to relegate his ´anti-communist cultural battle´ in the face of China´s status as the main economic partner and the exuberant portfolio of investments in renewable and non-renewable energies. With a qualitative methodological design, this paper presents two sections: the first begins with the declaration of the bilateral link as a strategic partnership and goes through the Petistas governments; the second focuses on the post-impeachment period and sustains the alliance despite Jair Bolsonaro´s speeches against Chinese ´communism´.The results are clear: the relationship between Brazil and China over the course of this century is unprecedented in the regional scenario and is highly unique. Each country sees in the other a first-rate partner to satisfy a set of interests that, at times, run parallel to political and commercial dimensions and, at others, are decoupled, with one of them prevailing above all: the economic one. For this reason, the short circuits that existed during Bolsonaro´s term did not divert the relationship from its usual path.